Hepcidin-to-Ferritin Ratio Is Decreased in Astrocytes With Extracellular Alpha-Synuclein and Iron Exposure - Cui, Juntao; Guo, Xinli; Li, Qijun; Song, Ning; Xie, Junxia (Frontiers in Cellular Neuroscience, 2020)
Astrocytes are the most abundant glial cells in the central nervous system (CNS). As indispensable elements of the neurovascular unit, they are involved in the inflammatory response and disease-associated processes. Alpha-synuclein (α-syn) is released into the extracellular space by neurons and can be internalized by adjacent astrocytes, which activates glial cells to induce neuroinflammation. We were interested in whether astrocyte-mediated neuroinflammation is modulated by intracellular iron status and extracellular α-syn. Our results showed that recombinant α-syn (1 μg/ml and 5 μg/ml) treatment for 24 h did not affect the expression of the iron transporters divalent metal transporter 1 (DMT1) and ferroportin 1 (FPN1), nor those of iron regulatory protein (IRP) 1 or IRP2. Several proinflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6 exhibited up-regulated mRNA levels in 5 μg/ml α-syn-treated astrocytes. TNF-α release was increased, indicating that inflammatory responses were triggered in these cells. Pretreatment with the iron-overload reagent ferric ammonium citrate (FAC, 100 μmol/L) for 24 h had no effects on mRNA levels and release of proinflammatory cytokines. Inflammatory responses triggered by α-syn were not affected by iron overload. The iron chelator desferrioxamine (DFO, 100 μmol/L) exerted suppressive effects on TNF-α mRNA levels, although no change was observed for TNF-α release. Hepcidin mRNA levels were down-regulated significantly in astrocytes co-treated with FAC and α-syn, although independent treatment with either FAC or α-syn did not alter hepcidin levels. In contrast, hepcidin mRNA levels were up-regulated in DFO and α-syn co-treated cells. As expected, ferritin protein levels were up-regulated or down-regulated with FAC or DFO treatment, respectively. Following the up-regulation of ferritin mediated by α-syn, hepcidin-to-ferritin levels were indicative of modulatory effects in α-syn-treated astrocytes with altered iron status. Therefore, we propose that the hepcidin-to-ferritin ratio is indicative of a detrimental response in primary cultured astrocytes experiencing iron and extracellular α-syn.